Determinación de la presencia de parásitos gastrointestinales zoonóticos en caninos de la ciudad de Loja - Mogrovejo Sichiqui, Miguel Angel (2023)
Parasitic diseases represent a zoonotic risk worldwide, mainly in underdeveloped countries, affecting health; and generating a high degree of vulnerability. This study aimed to determine the presence of zoonotic gastrointestinal parasites in canines in the city of Loja and to know which factors could be associated (food, age, water, deworming, coexistence, environment, body condition) employing the statistical test called Fisher's exact test. For this purpose, 100 samples of canine feces were collected and analyzed by copro-parasitic techniques (direct smear and flotation with zinc sulfate). We determined that 35 % (35/100) of the animals had gastrointestinal parasites, of which 91.4 % (32/35) were positive for zoonotic parasites. Mainly nematodes were reported at 93.8 %, then cestodes at 6.3 %; it is worth mentioning that the most frequent order/genus of parasites belonged to Strongyloides, 71.9 % of the samples, Toxocara canis 21.9 % and Dipylidium caninum, 6.3 %. In the statistical part, we determined no significant relationship (p>0.05). However, we reported the existence of zoonotic gastrointestinal parasites that are considered a risk to public health in the city of Loja, affecting pets and, therefore, their owners, showing a lack of management in the routine control of endoparasites. Keywords: Gastrointestinal parasites, zoonotic, flotation, associated factors